In-operando optical imaging of temporal and spatial distribution of polysulfides in lithium-sulfur batteries. (January 2015) - Sun, Yongming; Seh, Zhi Wei; Li, Weiyang; Yao, Hongbin; Zheng, Guangyuan; Cui, Yi
Abstract: Understanding the behavior of soluble intermediate lithium polysulfide species is vitally important for improving the electrochemical performances of lithium-sulfur batteries. Herein we explore a simple in-operando lithium-sulfur cell design to enable direct visualization of the formation of the soluble polysulfide species and their temporal and spatial distribution over the entire discharge/charge cycle under an optical microscope. Our results reveal detailed evidence of electrochemical degradation in lithium-sulfur batteries and help us to understand the improvements in electrochemical performances using advanced lithium-sulfur cell designs. As examples, we show that a cathode consisting of hollow sulfur nanoparticles with a conductive polymer poly(3, 4-ethylenedioxythiophene) (PEDOT) coating exhibits significantly reduced dissolution of polysulfides into the electrolyte, and thus superior electrochemical performance could be achieved. Moreover, the trapping of soluble polysulfide species in the cathode side was also confirmed in our designed in-operando lithium-sulfur cell with a Nafion modified separator. Graphical abstract: Highlights: A simple in-operando lithium-sulfur cell design has been explored. The formation of the soluble polysulfide species can be directly observed. The temporal and spatial distribution of polysulfide species can be visualized. The trapping of polysulfides in lithium-sulfur cells can be easily investigated.